Project Management : A Managerial Approach - Meredith, Jack R.; Mantel, Samuel J. (New Delhi Wiley India (Pvt.) Ltd., 2015)
English Document.
Include Figures and Indexes.
A Managerial Approach.
Keywords: Project management -- Microsoft Project -- Crystal ball (Computer file)